2011
DOI: 10.1002/ar.21477
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Features and Glycoconjugate Pattern of Rabbit Intestine are Affected by Particle Size of Pelleted Diets

Abstract: Feed particle size effects on morphology and glycoconjugate pattern was investigated in the rabbit intestine. Rabbits fed with fine particles (2 mm) displayed more irregularly shaped, higher duodenal villi and deeper crypts in distal colon as well as higher number of goblet cells than coarse (8 mm) fed ones. Brush border expressed: (i) in duodenum, neutral/sulfated glycoconjugates and glycans binding MAL II, SNA, Con A than KOH-sialidase-PNA and DBA reactivity in fine and coarse fed rabbits, respectively, (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Based on our results, we can also say that the addition of different types of fat does not affect the histological structure of the digestive tract, which is probably more dependent also on the fiber and particle size of the feed. Desantis, et al [47] reported that rabbits fed with more finely milled particles (2 mm) in feed had irregularly shaped and significantly longer villi in the duodenum compared to rabbits, of which particles in the feed were roughly ground (8 mm). Beside the longer villi, rabbits fed with finely milled feed also had deeper crypts in the duodenum and caecum, and were significantly deeper in the colon [47]; short intensive feed restriction increased villi height and crypt depth [48].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we can also say that the addition of different types of fat does not affect the histological structure of the digestive tract, which is probably more dependent also on the fiber and particle size of the feed. Desantis, et al [47] reported that rabbits fed with more finely milled particles (2 mm) in feed had irregularly shaped and significantly longer villi in the duodenum compared to rabbits, of which particles in the feed were roughly ground (8 mm). Beside the longer villi, rabbits fed with finely milled feed also had deeper crypts in the duodenum and caecum, and were significantly deeper in the colon [47]; short intensive feed restriction increased villi height and crypt depth [48].…”
Section: Discussionmentioning
confidence: 99%
“…Romero et al [ 11 ] also reported that finely ground (1.5 mm), dehydrated alfalfa increased the villous height and decreased the crypt of jejunum when compared with grinding at 4.5 mm. Desantis et al [ 46 ] reported that rabbits fed fine particles (2 mm) displayed more irregularly shaped, greater duodenal villi and deeper crypts in the distal colon as well as a greater number of goblet cells than rabbits fed coarse (8 mm) particles. The superfine grinding of fibers (100 and 10 μm) had a somewhat detrimental effect on small intestine morphology in present study.…”
Section: Discussionmentioning
confidence: 99%
“…Lectin histochemistry, when combined with enzymatic digestion and chemical treatment, can be a valuable tool to highlight changes in the glycosylation of intestinal mucins (Desantis et al, 2011) and thus is valuable for diagnosis of diseases. The mouse is frequently used as animal model to investigate the mechanisms of development of intestinal disease induced by supply of drugs, diets, and genetic modification (Erdelyi et al, 2009;Fu et al, 2011;An et al, 2007).…”
Section: Introductionmentioning
confidence: 99%